Marriage Dispensation in Underage Marriage: A Case Study at the Purwokerto Religious Court - Syufa'at, Syufa'at (Al-Manahij: Jurnal Kajian Hukum Islam, 2022)
The purpose of marriage is to make family in happy and eternal according to the purpose of Law Number 1 of 1974, and the state has set a marriage age limit. Problems occur because there are many cases of marriage dispensation with decisions being granted which sometimes contradict the purpose of marriage. This study discusses the marriage dispensation decision at the Purwokerto Religious Court in 2018 with 108 decisions. The results show that there are two main factors that make judges allow children to marry through marriage dispensation. The first factor considered by the panel of judges, namely the existence of such a close relationship between the prospective groom and the prospective bride that causes the parents of each prospective bride and groom to worry that their child will fall into things that will be detrimental. The second reason assessed by the panel of judges was that the bride and groom were pregnant. In order to reduce the practice of marriage dispensation, pre-marital guidance, counseling through recitation is a psychological and mental preparation to achieve the purpose of marriage.